1995
DOI: 10.1099/00222615-42-4-258
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of Escherichia coli O157: H7 isolates by pulsed-field gel electrophoresis and plasmid DNA analysis

Abstract: Summary. Foods of bovine origin have been identified as sources of Escherichia coli 0157:H7. Genomic DNA of E. coli 0157:H7 isolates from patients (six isolates), food samples (18 isolates from ground beef and six isolates from raw milk) and calf faecal samples (3 1 isolates) were characterised by pulsed-field gel electrophoresis (PFGE) and plasmid DNA analysis. These isolates originated from different locations in the USA during 1992 and 1993. Twenty-one distinct genomic profiles were generated from the 61 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 6 publications
4
34
0
Order By: Relevance
“…is method has widely been used as a molecular subtyping method of STEC strains, including O157, due to its high discriminatory power and good reproducibility (Bohm and Karch, 1992;Meng et al, 1995). In the present study, it was shown that epidemiologically unrelated O157 E. coli isolates produced very similar XbaI restriction profiles.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…is method has widely been used as a molecular subtyping method of STEC strains, including O157, due to its high discriminatory power and good reproducibility (Bohm and Karch, 1992;Meng et al, 1995). In the present study, it was shown that epidemiologically unrelated O157 E. coli isolates produced very similar XbaI restriction profiles.…”
Section: Discussionsupporting
confidence: 51%
“…coli strains of the O157 serogroup show a clonal nature and highly sensitive molecular biology-based subtyping methods are needed to compare and to differentiate unrelated strains isolated from different sources (Whittam et al, 1988;Feng et al, 1998). Several methods have been used for genetic analysis of STEC O157 and among them differentiation of chromosomal DNA based on restriction fragment length polymorphism (RFLP) and pulsed-field gel electrophoresis (PFGE) appear to be the most powerful techniques that provide the greatest discrimination and reproducibility (Bohm and Karch, 1992;Meng et al, 1995). e aim of this study was to analyse, using polymerase chain reaction (PCR), the presence of the STEC-associated virulence genes stx1, stx2, eaeA, ehly, and tir, in E. coli strains of the O157 serogroup isolated from cattle and from pigs.…”
mentioning
confidence: 99%
“…Since the XbaI restriction enzyme site occurs infrequently in the O157 genome, it is frequently used with PFGE for typing of this organism (3,4,7). Although PFGE has successfully been used to support outbreak investigations, it may be impossible to fully resolve all bands on a gel under a single set of conditions, making interpretation and comparisons difficult (7,8,10).…”
Section: Discussionmentioning
confidence: 99%
“…PFGE analysis represents a "gold standard" in epidemiological studies of diverse bacterial pathogens including other E. coli groups (2,18,19,26). In the present study, XbaI-generated DNA fingerprints proved to be more sensitive than RAPD Table 1 and are indicated at the top.…”
Section: Discussionmentioning
confidence: 99%